GE_GERICHTE C/8814/2014 vom 20. Mai 2016 - GE Cour de justice (2016)
DIVORCE; INDEMNITÉ ÉQUITABLE; FONCTIONNAIRE; ORGANISATION INTERNATIONALE; PRÉVOYANCE PROFESSIONNELLE; OBLIGATION D'ENTRETIEN | CC.122; CC.124; CC.4